Đánh giá tác động của đổi mới sáng tạo đối với thu nhập dân cư và khuyến nghị chính sách: góc nhìn từ chỉ số đổi mới sáng tạo cấp địa phương - Phan Thị Bích, Nguyệt; Phạm Dương Phương, Thảo; Nguyễn Thị Hồng, Nhâm; Lê, Văn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This article assesses the impact of components in the provincial innovation index on average income and income groups (from groups 1 to 5) of 63 provinces and cities in 2023. We employ the linear regression method to evaluate impacts of provincial innovation sub-indexes on levels of national income of Vietnam. The empirical results show that population income has a positive impact on indicators of infrastructure, market development, business development, knowledge–creative–technology products and the impacts of innovation. Results indicate factors that each local authority needs to improve the quality of innovation and improve population income, which are factors of institutions, human capital, and research and development. In accordance with empirical findings, we propose policy recommendations to improve the innovation capacity of each locality, such as: (i) high-quality human resources; (ii) international cooperation in training; and (iii) promoting scientific, technological, and innovative activities. In particular, local authorities play an important role in improving the quality of innovation as well as people’s income.